ANALISIS PENGENDALIAN INTERNAL PERSEDIAAN PADA GIANT SAMARINDA CENTRAL PLAZA - Akhmad Zeki (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
Inventory is one of the important assets owned by the company. Because inventory is an asset, good internal control should be performed to keep the inventory from the bad things that may happen. Therefore, the purpose of this study is to analyze the internal control performed, in order to get a clear picture of the internal control inventory applied. To obtain data the authors do the data collection required the author using data collection tools in the form of Internal Control Quesioner (ICQ) and bibliography. The author obtained the data through obesrvasi and documentation in the field. From the result of the research, it is concluded that the internal inventory control at giant samarinda central plaza is good enough, but still has lack of firmness in the separation of task and employee professionalism. Keywords: Internal Control, Inventory, Analysis